Supramolecular design based activatable magnetic resonance imaging. Issue 2 (12th November 2020) - Geng, Wen‐Chao; Zheng, Zhe; Guo, Dong‐Sheng
Abstract: Magnetic resonance imaging (MRI) has been widely used in clinical diagnosis. In recent years, activatable MRI probes responding to specific changes in their microenvironment have been developed. The signal of the MRI probe can be modulated based on supramolecular design, which can include properties such as self‐assembly and molecular recognition. In this review, we summarize the activatable MRI probes based on the design principles of supramolecular chemistry. We also discuss the current challenges and the future perspectives for how activatable MRI can achieve more extensive clinical applications for cancer therapy. Abstract : The activatable magnetic resonance imaging based on the design principles of supramolecular chemistry has been summarized and discussed.